The growth of Paraserianthes falcataria at three different plant ages and soil thickness classes on reclamation sites of post-coal mining areas in East Kalimantan, Indonesia (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Mulyadi, Ruhiyat D, Aipassa MI, Hardwinanto S. 2022. The growth of Paraserianthes falcataria at three different plant ages and soil thickness classes on reclamation sites of post-coal mining areas in East Kalimantan, Indonesia. Biodiversitas 23: 1930-1937. Sengon (Paraserianthes falcataria (L.) Nielsen syn. Falcataria moluccana (Miq.) Barneby & J.W. Grimes) is a fast-growing species commonly used for reclamation of post-coal mining areas in East Kalimantan. The study aimed to determine the impact of different thicknesses of topsoil applied at some reclamation sites after coal mining activities on the growth of P. falcataria. Three coal mining companies were chosen as study areas, i.e., PT Bukit Baiduri Energi (BBE), PT. Mahakam Sumber Jaya (MSJ), and PT. Kaltim Prima Coal (KPC). The regolith soil layer at the reclamation site had three thickness classes (0-10 cm, 0-30 cm, 0-100 cm), and the P. falcataria growing on reclamation had three ages, i.e.,< 2 yrs old (initial growth phase), 2-5 yrs old (tending phase), and > 5 yrs old (independent growth phase). The number of surviving plants, plant height, and plant stem’s diameter were recorded, and the data were analyzed using ANOVA and the least significant difference at 5% level. The results showed that no significant difference in the number of trees among different ages of P. falcataria plantation was found at MSJ. In contrast, at BBE and KPC the number of surviving trees decreased significantly with the increasing plant age. The growth of the plant (height, diameter) increased significantly along with plant age in all sites. The interaction between the top soiling thickness factor and plant age factor produced no different result in plant growth except for plant height at BBE. The P. falcataria plants had not been able to lower the surface soil density in the land reclamation area.